Reintegration of State Financial Management Through the FARAH Model: An Accounting Study of Inmates at Lapas Parepare - Farah Nabilah Ramadhani; Marwah Yusuf; Lusiana Kanji (Manunggal Halim Jaya, 2026)
This research aims to analyze the role of state financial management in supporting the development and social reintegration of prisoners at Class IIA Parepare Correctional Facility, as well as to examine the effectiveness of the FARAH model (Financial Management, Accountability, Rehabilitation, Awareness, and Holistic Approach). This model is positioned as an integrative framework that links the technical aspects of budget management with social needs in Lapas. The research uses a qualitative method with a phenomenological approach based on Alfred Schutz's sociology. Data is obtained through in-depth interviews, observations, and document analysis, and its validity is tested through triangulation and member checking. Research results show that budget management in Parepare Correctional Facility has been carried out according to procedures, but still faces challenges such as overcapacity, limited resources, and partial rehabilitation programs. The implementation of the FARAH model (Financial Management, Accountability, Rehabilitation, Awareness, and Holistic Approach) offers an integrative solution: Financial management serves as the material basis that ensures basic needs and rehabilitation space are met, while Accountability builds transparency and trust as a form of state legitimacy. Rehabilitation opens up space for the transformation of values and behaviors, Awareness fosters moral and existential consciousness, and the Holistic approach unites all elements in a cross-sectoral collaboration network that strengthens social integration.